Punjab Jails Department: Organizational Structure and Functions (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The Department of Jails in Punjab plays a pivotal role in the administration, management, and reform of prisons across the state. Its organizational structure is designed to ensure effective governance, security, and rehabilitation of inmates while maintaining coordination with other government agencies. This study highlights the hierarchical framework of the department, detailing the roles and responsibilities of officials at various levels—from the Inspector General of Prisons to jail superintendents and supporting staff. It also examines the functional dimensions of the department, including custody and care of prisoners, maintenance of law and order within prisons, rehabilitation and reformation initiatives, and administrative support systems. By analyzing the structure and functions together, the paper underscores how the department balances discipline with reformatory measures, and addresses the challenges of overcrowding, human resource limitations, and infrastructural constraints. The study thus provides a comprehensive understanding of the Punjab Jails Department as an essential institution in the state’s justice and correctional system.